The pion mass and decay constant at three loops in two-flavour chiral perturbation theory - Johan Bijnens; Nils Hermansson Truedsson (Journal of High Energy Physics, 2017)
Abstract A calculation of the pion mass and decay constant at NNNLO in two-flavour chiral perturbation theory is presented. The results are cross-checked by using both the exponential and square root parametrizations of the Goldstone matrix field, as well as by comparing to the known leading log coefficients of the two quantities. A small numerical study of the quark mass dependence is performed, and for a physical quark mass there is good agreement with lower order results.